Collection Development of Digital Archives in India: A Case Study of Jadavpur University (LIS TODAY, 2022)
The free flow of information is a fundamental principle for bridging the gaps between have and have  not. ICT has a major impact of materials for research. Innovationin ICT has brought radical changes in the way  information is generated, stored, processed and disseminated. Recent advances in converging technologies  especially Internet and web technology has paved the way to create the open access archives on repositories. The  objective of the open access movement is to make scholarly articles freely available in digital form to anyone  anywhere in the world. The open access and open archives movement, the need for changes in the scholarly  communication to remove barriers to access.
Keywords: Jadavpur University; Institutional Repositories; Digital Libraries; Open Access; DOAR; IR; Digital Contents